2008 IEEE International SOC Conference 2008
DOI: 10.1109/socc.2008.4641525
|View full text |Cite
|
Sign up to set email alerts
|

A higher-order mismatch-shaping method for multi-bit Sigma-Delta Modulators

Abstract: Abstract-Mismatch-shaping Dynamic Element Matching (DEM) methods are extensively used in multi-bit Sigma-Delta Modulators (SDM) to reduce the effects of element mismatches. To date, only first and second-order mismatch-shaping DEM techniques have been reported in the literature. In this paper, a higher-order mismatch-shaping DEM method is reported, which is an extension of the known vector-feedback mismatch-shaping technique. Example simulation results are presented for thirdorder and fourth-order mismatch-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, realizing DEM designs of order >2 in lowpass and >4 in bandpass is difficult to achieve. In [5], the authors outline the use of a ∆∑ modulator structure to provide high order mismatch shaping in a vector feedback DEM design. The work in [6] details a significant advancement with the development of a 4 th order lowpass vector feedback DEM.…”
Section: Introductionmentioning
confidence: 99%
“…However, realizing DEM designs of order >2 in lowpass and >4 in bandpass is difficult to achieve. In [5], the authors outline the use of a ∆∑ modulator structure to provide high order mismatch shaping in a vector feedback DEM design. The work in [6] details a significant advancement with the development of a 4 th order lowpass vector feedback DEM.…”
Section: Introductionmentioning
confidence: 99%
“…Several DEM techniques exist such as Data Weighted Averaging (DWA) [1], Butterfly-shuffler [2], Tree structure [3] and Vector Feedback [4] but so far the mismatch shaping provided by these schemes is limited to second order. Research has shown that Vector Feedback DEM has the potential to provide higher orders of mismatch shaping [5], however hardware designs with stable implementations or orders greater than 2 remain difficult to achieve for high frequencies and low silicon area overheads. In particular, the area occupied by the DEM circuitry is known to increase exponentially with higher N-bit DAC sizes and this typically limits the number of bits in the DAC to between 4 and 6 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The solution to this is to use higher order DEM schemes, however the implementation of these schemes is not trivial as orders greater that 2 suffer from instability. One method of using higher order noise shaping is presented in [5]. Here the author demonstrates behavioral simulations of 4th order noise shaping filters that achieve very high resolutions for low-pass signals when dealing with a static mismatch of 1%.…”
Section: Introductionmentioning
confidence: 99%